Reconstruction of Scalp Wounds with Exposed Calvarium Using a Local Flap and a Split‐Thickness Skin Graft: Case Series of 20 Patients. Issue 3 (18th January 2014) - Aldabagh, Bishr; Cook, Jonathan L.
<x xml:space="preserve">Abstract</x> Objectives To describe the design, execution, outcomes, and advantages of a combined flap and split‐thickness skin graft reconstructive technique for the repair of wounds of the scalp with exposed bone after Mohs micrographic surgery. Materials and Methods An analysis of the combined flap and graft technique of 20 scalp defects ranging in size from 6.25 to 37.6 cm2 is provided. Surgical defects and patient characteristics are described. Follow‐up information is reviewed, and complications and final aesthetic results are reported. Results Twenty patients with 20 tumors on the scalp (16 squamous cell carcinoma, 2 basal cell carcinoma, 1 Merkel cell carcinoma, and 1 malignant fibrous histiocytoma) were treated using Mohs micrographic surgery. A combined flap and graft technique was successfully employed with good aesthetic outcomes in all 20 patients with broad scalp defects. One postoperative complication of approximately 20% skin graft necrosis was noted. One methicillin‐resistant Staphylococcus aureus postoperative wound infection occurred but resolved without sequelae with appropriate antibiotic treatment. Conclusion The described flap and graft reconstructive technique is a reproducible, one‐stage procedure for the reconstruction of medium to large scalp defects with exposed bone, obviating the need for more‐complicated, costly, time‐consuming procedures. Limitations Small sample size, descriptive study.